‘Diving for dope’: identity in submarine drug policing at the ‘maritime gateway to Europe’ - Eski, Yarin (European journal of criminology, 2022)
This article offers an ethnographic account of everyday identity (re)configuration in submarine policing by the Dutch Customs Diving Team (CDT) officers of illegal underwater drug trafficking in the Port of Rotterdam (PoR). In so doing, it explores what it means to perform drug inspections that depend on international collaboration and intelligence sharing, and also depend on the cooperation of ships’ crews, enabling the CDT to deal with challenging submarine circumstances. The findings emerge from a qualitative analysis, using an Othering framework, of data collected during fieldwork in 2011 in the PoR. The main argument of this contribution is that to prevent drug trafficking from entering in the port (and its European hinterland) and by legitimately interrupting the trade flow, the CDT must become a justifiable intervention itself. However, given the low number of drug seizures since the CDT’s inception, its legitimacy and efficacy are called into question at a time of hypersecuritization on the one hand and austere policing on the other; a bifurcating context in which CDT officers feel the need to (re)configure a superior policing Self through an inferior policed Other for which (discriminating) stigmas that exist about drug trafficking, maritime shipping and (counter-narcotics) policing are (unwillingly) used and amplified.